Determination of anterior femoral bowing to length ratio in Iranian population - Amanjani, Abdol Rashid; Zandi, Reza; Samandari, Saeed Saber (Researcher Bulletin of Medical Sciences, 2020)
Due to the existence of different races and ethnicities and their different life styles, anatomical structure of people vary from one region of the world to another. The goal of this study is to determine the anterior femoral bowing to length ratio, which can be useful for planning major medical and therapeutic projects as well as designing medical equipment (including nails, orthoses and prosthetics). Lateral X-rays of femur bones of 250 patients who referred to Taleghani hospital in recent years (2011-2016) were retrieved from hospital archives and studied. 150 patients were females and 100 were males, ages ranging from 16 to 57 years old. All patients were Iranians with different ethnical backgrounds that referred to radiology centers of Tehran and Taleghani hospital and their records were saved in these centers archive. Based on femoral length, X-rays were categorized into eight groups; 300mm, 320mm, 340mm, 360mm, 380mm, 400mm, 420mm and 440mm, which are standards for manufacturing femoral nails in Iran as well as imported nails to Iran. Results showed significant difference compared to available femoral nails on the Iranian market, which indicates that these nails are not standard for Iranian population. Data analysis was based on anterior femoral bowing to length ratio alone. Gender and age were not considered for data analysis in this study and results were conclusive for all ages and genders.